55 Huntington Avenue, ca. 1959 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of 55 Huntington Avenue, located at the southwest corner of Huntington Avenue and Exeter Street. Signage adorns 55 Huntington Avenue. The southeast corner of the Copley Square Hotel is visible along the upper-right side of the photograph. Street lamps and traffic lights line Huntington Avenue, and automobiles fill the street. Pedestrians are also included in the photograph. 7 3/4 x 7 7/16, 9 7/8 x 7 15/16 overall Photographs